Special duty : a history of the Japanese intelligence community - Samuels, Richard J. (Ithaca : Cornell University Press, 2019)
"Two decades into the 21st century, after more than a century of dangerously uneven performance that contributed to national devastation and often uncomfortable subordination to their powerful U.S. ally, Japanese leaders have begun to reinvent their nation's flawed intelligence community"--
Driving intelligence -- Expanding special duties (1895-1945) -- Accommodating defeat (1945-1991) -- Tinkering with failure (1991-2001) -- Reimagining possibilities (2001-2013) -- Reengineering the intelligence community (2013- ) -- The past and future of Japanese intelligence.
First published 2019
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Intelligence service -- Japan -- History